Resource-based theory of competitive advantage - a framework for pharmacy practice innovation research - Holdford DA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
A growing body of research demonstrates the effectiveness of evidence-based pharmacy practice, but too many practice innovations fail to survive past the initial implementation and study phase. This paper presents the resource-based theory of competitive advantage as a framework for describing, understanding, and predicting the adoption and dissemination pharmacy service innovations into routine practice. The theory argues that the sustainability of any business innovation (e.g., pharmacy service) is based upon (1) the internal resources of the firm offering it, (2) the firm's capabilities in using those resources, (3) the competitive advantage to the firm of its resources and capabilities, (4) the attractiveness of the market in which it competes, and (5) the innovation's contribution to financial performance of the firm. This paper argues that the resource-based theory of competitive advantage provides a foundation for comparing findings from different research frameworks and studies relating to innovations in services, service processes, and service business models. The paper also poses a number of research questions related to the theory that can be used to further the literature about pharmacy practice innovations. Finally, it makes a case that competition is a fundamental aspect of pharmacy practice and the resource-based theory of competitive advantage can serve as a general theory for studying innovations in pharmacy practice and in the social and administrative sciences.